DEVELOPMENT AND VALIDATION OF THE METHOD OF KINETIC EVALUATION OF MEDICAL SUBSTANCE TOPIRAMAT DISSOLUTION BY LASER DIFFRACTION OF LIGHT METHOD - E. V. Uspenskaya; A. A. Keshishian; M. V. Nikiforova; T. V. Pletneva; A. V. Syroeshkin (Разработка и регистрация лекарственных средств)
Solubility is the most important quality indicator, reflecting the physicochemical properties of active pharmaceutical ingredients (APIs). Prior to the release of API, solubility is one of the key factors affecting the efficacy and safety of drugs. Therefore, the directed development of new drugs with predetermined properties (drug design) should be basedon solubility of candidate substances and be taken into account when evaluating the bioequivalence of generic drugs branded, including in vitro - in vivo correlation. Given that the pharmacopeia regulation of the test for the solubility of API is reduced to a visual estimate and approximate solubility, we developed a kinetic dissolution evaluation method by laser diffraction and performed statistical analysis of the results obtained under repeatability conditions.